Program Satu Hari Berbahasa Indonesia (Upaya Meningkatkan Kemampuan Bahasa Baku Anak di TK Mawar Cikalong - Masitoh, Imas; Kuswandi, Aang Andi (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
Mawar Kindergarten - Cikalong is one of the schools that implements the one-day Indonesian language program. This program aims to make children able to communicate with a wider environment because Indonesian is the main communication medium for the Indonesian people. The research method used is descriptive qualitative research. The results showed that 1) The implementation of the one-day Indonesian language program for children aged 5-6 years at Kindergarten Mawar - Cikalong has been running quite well. This can be seen from the comparison of the number of children who are able to communicate, ask questions, express opinions, and mention objects around them using Indonesian well more than those who are not good enough; 2) The obstacle experienced in implementing the program is that the teacher has not effectively explained the importance of using Indonesian to children so that often children still use Sundanese when the learning process in class.